(untitled) (Clinics, 2012)
OBJECTIVE: This study aimed to identify novel GATA5 mutations that underlie familial atrial fibrillation. METHODS: A total of 110 unrelated patients with familial atrial fibrillation and 200 unrelated, ethnically matched healthy controls were recruited. The entire coding region of the GATA5 gene was sequenced in 110 atrial fibrillation probands. The available relatives of the mutation carriers and 200 controls were subsequently genotyped for the identified mutations. The functional effect of the mutated GATA5 was characterized using a luciferase reporter assay system. RESULTS: Two novel heterozygous GATA5 mutations (p.Y138F and p.C210G) were identified in two of the 110 unrelated atrial fibrillation families. These missense mutations cosegregated with AF in the families and were absent in the 400 control chromosomes. A cross-species alignment of GATA5 protein sequence showed that the altered amino acids were completely conserved evolutionarily. A functional analysis revealed that the mutant GATA5 proteins were associated with significantly decreased transcriptional activation when compared with their wild-type counterpart. CONCLUSION: The findings expand the spectrum of GATA5 mutations linked to AF and provide novel insights into the molecular mechanism involved in the pathogenesis of atrial fibrillation, suggesting potential implications for the early prophylaxis and personalized treatment of this common arrhythmia.